Five Poems - Adrian GRAFE (E-REA)
The first four of the five texts included here, none of them long, were all inspired by university poetry-writing workshops I’ve either attended (‘For Saint-Exupéry’) or given (the following three). Concerning ‘For Saint-Exupéry’, the instruction was to write a poem containing the word ‘graveyard’. ‘Are You Ready’: write a poem beginning ‘Are you ready to’. ‘Summers in Nettlebed’: the requirement was to write a villanelle. ‘New Vaccine’: write a poem in quatrains on the theme of discovery (theme inspired by Brian Patten’s poem ‘The Small Dragon’ which begins ‘I’ve found a small dragon in the woodshed’). The latter three poems were written during the workshops, as in fact I do the exercises I set and write along with the students in real time. I have given poetry-writing workshops to third-year English students several times since 2016, either as part of the Printemps des Poètes events at Artois, co-organised with my colleague Mireille Demaules, our librarians and staff of our Service culture, or as ‘stand-alone’ sessions. I would add, after Louise Glück who states in her introduction to Proofs & Theories: Essays on Poetry (1994) that her poetry and her scholarship spring from the same impulse that, to me, both teaching and research, as I try to practise them, are in themselves deeply creative acts.Finally, a song lyric (for the source cf below). I was kindly invited by Claire Hélie when she and Elise Brault were leading a Paris III POEM workshop session on dialect poetry to recite a poem, and recited the lyrics of ‘Gunman’ as a poem. It is intended as a sort of affectionate imitation (in no wise a parody) of Linton Kwesi Johnson, whose ‘Inglan is a Bitch’ I have taught.